The western universalism v. cultural relativism debate on human rights and islam: An ‘Aqīdah-based approach - Muhammadin, Fajri Matahati; Mohd Kamal, Mohd Hisham (University of Malaya, 2019)
The human rights discourse of (Western) universalism versus cultural relativism in international law becomes interesting when Islam is put into the equation. Scholars incline to either side of the debate while trying to have something in between to bridge the differences. This article uses a literature doctrinal method and does not use the ‘third-person view’ used by most scholars. Rather, this article uses an ‘aqīdah approach to analyze the challenge faced by Muslim international law scholars. It is argued that inclining to either universalism or relativism is against the Islamic ‘aqīdah (creed). Rather, the position which is correct according to the Islamic ‘aqīdah is to take a third path, namely Islamic universalism as a way forward